Distribution of complete CRISPR-Cas systems in vibrio cholerae and its effect on presence of plasmid derived contigs in complete genome assemblies - Reza, Ratul (BRAC University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2023.